Is White Always Right? Skin Color and Interdating Among Whites - Santana, Emilce (Race and social problems, 2020)
The burgeoning literature on skin color stratification highlights how skin color is associated with disparities in outcomes such as socioeconomic status, health, and intergroup relationships among ethnoracial minorities. However, there is a limited body of work that suggests that darker skin color is also associated with differing outcomes among whites in spite of their position as the socially dominant group of the U.S. This study uses the National Longitudinal Survey of Freshmen to examine how skin color, among whites, relates to their likelihood of dating ethnoracial minorities. The results show that darker skin color is associated with greater odds of dating Latinos and Asians. The results also suggest that there is a non-linear relationship between whites’ skin color and their likelihood of dating blacks. The author argues that because darker skin color connotes lower status due to its affiliation with non-whiteness, darker skin color among whites can lead to greater interactions with ethnoracial minorities. However, there may be an exception when dating blacks. This study highlights a possible underlying mechanism, ethnoracial ambiguity among whites, that shapes current ethnoracial relations, which has long-term implications for the future of intergroup boundaries.